LABOUR MOVEMENTS IN THE GLOBAL SOUTH AND THE STRUGGLES AGAINST NEOLIBERAL GLOBALISATION: THE CONGRESS OF SOUTH AFRICAN TRADE UNIONS (COSATU) EXAMPLE - Aliu, Monday (European Scientific Journal, ESJ, 2015)
The paper examines the possibilities of labour movements in the Global South playing a strategic and significant role in the struggle against the onslaught of neoliberal globalisation on labour and labour movements, drawing experiences from the Congress of South African Trade Unions (COSATU).The paper is basically descriptive and analytical and employs data obtained mainly from secondary sources. The paper contends that labour is core to the sustenance of the neoliberal capitalist system, especially its unending quest for profit maximisation, primitive accumulation and expansion of capital globally. Yet, complexities and contradictions inherent in the current neoliberal globalisation process have partly caused the structural deconstruction and dislocation of labour globally. In the Global South, the disorganisation of labour movements, job causalisation and informalisation, low wages, poor working conditions, mass retrenchment, erosion of workers’ rights, among others are obvious outcome of the attack of corporate capital on labour. Given the entrenched power of capital, the poverty conditions, and seeming failure of governments in the Global South to check the excesses of neoliberalism, there is the tendency to conclude that the prospect for organised labour movements to resist the current attack of neoliberal globalisation and corporate capital is hopelessly lost. However, the paper argues that given the seeming success of the COSATU experience, what is required is an organised programme that engages and mobilises the diverse societal movements and forces opposed to the threat corporate capital pose to society into one formidable block and the inclusion of the unorganised informal sector in the struggle.